2013
DOI: 10.1128/mbio.00244-13
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Binary Toxin CDT Induces Clustering of the Lipolysis-Stimulated Lipoprotein Receptor into Lipid Rafts

Abstract: Clostridium difficile is the leading cause of antibiotics-associated diarrhea and pseudomembranous colitis. Hypervirulent C. difficile strains produce the binary actin-ADP-ribosylating toxin CDT (C. difficile transferase), in addition to the Rho-glucosylating toxins A and B. We recently identified the lipolysis-stimulated lipoprotein receptor (LSR) as the host receptor that mediates uptake of CDT into target cells. Here we investigated in H1-HeLa cells, which ectopically express LSR, the influence of CDT on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…We then used LSR Ig -His 6 as prey protein in a GST pulldown assay and a GST fusion of the RBD from CDTb (amino acids 677-876) as bait. LSR-dependent cell surface-binding of GST-RBD was shown previously (31). As shown in Fig.…”
Section: Cdt Interacts With the Extracellular Ig-like Domain Of Lsr-supporting
confidence: 64%
See 3 more Smart Citations
“…We then used LSR Ig -His 6 as prey protein in a GST pulldown assay and a GST fusion of the RBD from CDTb (amino acids 677-876) as bait. LSR-dependent cell surface-binding of GST-RBD was shown previously (31). As shown in Fig.…”
Section: Cdt Interacts With the Extracellular Ig-like Domain Of Lsr-supporting
confidence: 64%
“…It is conceivable that the endocytosis of LSR is triggered also by other membrane proteins, which might form a complex with LSR. We found recently that LSR accumulates in lipid rafts upon binding of CDTb (31). Interestingly, Wigelsworth et al (43) found that the lipid raft-associated protein CD44 (cluster of differentiation 44 protein) is crucial for CDT uptake into host cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has also been reported that in monolayers of Caco-2 cells, transepithelial resistance (TER) is decreased by the formation of pores by Ib oligomer insertion into the cell membrane (34). Papatheodorou et al (35) have shown by fluorescence microscopy that a_CDTb can induce the clustering of LSR into subcompartments of the plasma membrane (lipid rafts), but they were not able to conclude whether the activated B component forms a heptamer that subsequently binds to the LSR receptor or whether the monomer first binds to the LSR receptor and then oligomerizes. We speculate that a_CDTb causes a high degree of LSR clustering on the HT-29 cell membrane, which might cause cytotoxicity through necrosis or disruption of the cell membrane similar to the cytotoxicity caused by Ib toxin.…”
Section: Discussionmentioning
confidence: 99%